Integrated profiling of global metabolomic and transcriptomic responses to viral hemorrhagic septicemia virus infection in olive flounder. Issue 71 (December 2017) - Cho, Se-Young; Kwon, Yong-Kook; Nam, Miso; Vaidya, Bipin; Kim, Seok Ryel; Lee, Sunghoon; Kwon, Joseph; Kim, Duwoon; Hwang, Geum-Sook
Abstract: Viral hemorrhagic septicemia virus (VHSV) is one of the most serious viral pathogen that infects farmed fish. In this study, we measured the replication of VHSV increased steadily at 9, 24, 72, and 120 h after infection and progression of necrosis was observed at 72 hpi. We performed transcriptomic and metabolomics profiling of kidney tissues collected at each infection time using Illumina HiSeq2000 and ultra-performance liquid chromatography/quadrupole time-of-flight mass spectroscopy to investigate the mechanisms of VHSV infection in the kidneys of olive flounder. A total of 13, 862 mRNA molecules and 72 metabolites were selected to identify the mechanisms of infection and they were integrated using KEGG pathway database. Six KEGG metabolic pathways, including carbohydrate metabolism, amino acid metabolism, lipid metabolism, transport and catabolism, metabolism of cofactors and vitamins, and energy metabolism, were significantly suppressed, whereas the immune system was activated by VHSV infection. A decrease in levels of amino acids such as valine, leucine, and isoleucine, as well as in their derivative carnitines, was observed after VHSV infection. In addition, an increase in arachidonic acid level was noted. Integrated analysis of transcriptome and metabolome using KEGG pathway database revealed four types of responses in the kidneys of olive flounder to VHSV infection. Among these, the mechanisms related to the immune system and protein synthesis were activated, whereas ATP synthesis and the antioxidant system activity were suppressed. This is the first study describing the mechanisms of metabolic responses to VHSV infection in olive flounder. The results suggest that the suppression of ATP synthesis and antioxidant systems, such as glutathione and peroxisome signaling, could be the cause of necrosis, whereas the activation of the immune system could result in the inflammation of kidney tissue in VHSV-infected olive flounder. Highlights: Metabolic responses to VHSV infection in olive flounder kidney was investigated. The integration of transcriptome and metabolome profiling was applied. Immune system via inflammation and protein synthesis were activated by VHSV infection. ATP synthesis and ROS antioxidant system were suppressed by VHSV infection.